Behavioural Cognitive Counseling to Improve Student Discipline - Budiastutik, Lilik; Budiyanto, Budiyanto; Nursalim, Much (Indonesian Journal of Educational Counseling, 2022)
This study aims to determine the increase in student discipline through cognitive behavioural counselling in SMP Negeri 1 Dawarblandong, Mojokerto Regency students. The research population was all students in class IX, and the research sample consisted of seven students with low levels of discipline. Test and post-test. Data analysis techniques using SPSS using experimental methods. In this research design, the researcher used an experimental model, namely a research design that contained a pre-test before being given treatment and a post-test after being given treatment.The results showed that the level of discipline of students of SMP Negeri 1 Dawarblandong with cognitive-behavioural counselling was practical. This is following the results of a score of 0.000, where 0.000 <0.05, then there is a significant difference between the pre-test and post-test data, meaning that there is a change after cognitive-behavioural counselling was carried out in improving student discipline SMP Negeri 1 Dawarblandong Mojokerto.